QUALITY ANALYSIS OF BAKERY PRODUCTS USING THE SIX SIGMA METHOD AND FAILURE MODE AND EFFECT ANALYSIS (FMEA) CASE STUDY ON CV. XYZ - Primahesa, Ibad Guntur; Ngatilah, Yustina (Transpublika Publisher, 2022)
CV. XYZ is a bakery production company which also contributes as a part of culinary industry. During producing, CV. XYZ faces problem regarding the high percentage of its defective products which namely blueberry blankon bread, banana chocolate bread, and coffee bread. This research aims to find out the value of DPMO and determining the value of Sigma for product quality by using Six Sigma method. Six sigma method was used since its able to control the number of defective products, find out the product defects by using Sigma value, improve product defects, and provide recommendations for improving the quality of product by using FMEA method on those three products. The result shows that DPMO value for Coffee Bread is 17,757 along with sigma value of 3,61. The DPMO value for blueberry blankon bread is 18,048 with sigma value of 3.60. Lastly, the DPMO value of chocolate banana bread is 17.644 with sigma value of 3.61. Thus, it is necessary to analyze the causes of quality defects and recommend solutions in order to improve the quality of products. Defects on product/s are caused by four factors which particularly human, material, method and machine. Hence, there are three ideas of proposed improvement on defect products based on FMEA.